A Time-Resolved Spectroscopic Investigation of a Novel BODIPY Copolymer and Its Potential Use as a Photosensitiser for Hydrogen Evolution - Cullen, Aoibhín A.; Heintz, Katharina; O'Reilly, Laura; Long, Conor; Heise, Andreas; Murphy, Robert; Karlsson, Joshua; Gibson, Elizabeth; Greetham, Gregory M.; Towrie, Michael; Pryce, Mary T. (Frontiers in Chemistry, 2020)
A novel 4,4-difuoro-4-bora-3a,4a-diaza-s-indacene (BODIPY) copolymer with diethynylbenzene has been synthesised, and its ability to act as a photosensitiser for the photocatalytic generation of hydrogen was investigated by time-resolved spectroscopic techniques spanning the ps- to ns-timescales. Both transient absorption and time-resolved infrared spectroscopy were used to probe the excited state dynamics of this photosensitising unit in a variety of solvents. These studies indicated how environmental factors can influence the photophysics of the BODIPY polymer. A homogeneous photocatalytic hydrogen evolution system has been developed using the BODIPY copolymer and cobaloxime which provides hydrogen evolution rates of 319 μmol h-1 g-1 after 24 hours of visible irradiation A novel 4,4-difuoro-4-bora-3a,4a-diaza-s-indacene (BODIPY) copolymer with diethynylbenzene has been synthesised, and its ability to act as a photosensitiser for the photocatalytic generation of hydrogen was investigated by time-resolved spectroscopic techniques spanning the ps- to ns-timescales. Both transient absorption and time-resolved infrared spectroscopy were used to probe the excited state dynamics of this photosensitising unit in a variety of solvents. These studies indicated how environmental factors can influence the photophysics of the BODIPY polymer. A homogeneous photocatalytic hydrogen evolution system has been developed using the BODIPY copolymer and cobaloxime which provides hydrogen evolution rates of 319 μmol h-1 g-1 after 24 hours of visible irradiation